50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-514
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings from efforts to model pulsed inductive theta-pinch plasmas via Particle-In-Cell

Abstract: A method is pursued to approximately model the electron energy distribution of pulsed inductive plasma devices with Particle-In-Cell code to elucidate formation physics during early times (t < 1 μs). Specifically, reported results from AFRL-Kirtland's pulsed inductive device, FRCHX, are used as a test case to validate results. An r-z slab approximation is outlined and gyro-frequency, Larmor radius, and E×B guiding center drift are verified against theory to within 1% difference. The analyses presented, using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In 2012, the PIC code was adopted to research the pre-ionization physical process for conical coils at Missouri University of Science and Technology. [11] They found that the bias field would inhibit the pre-ionization process of plasma if the electric field is mismatched.…”
mentioning
confidence: 99%
“…In 2012, the PIC code was adopted to research the pre-ionization physical process for conical coils at Missouri University of Science and Technology. [11] They found that the bias field would inhibit the pre-ionization process of plasma if the electric field is mismatched.…”
mentioning
confidence: 99%